Dental Modifications in a Skeletal Sample of Enslaved Africans Found at Lagos (Portugal) - Wasterlain, S. N. (2016)
An archaeological intervention in Valle da Gafaria (Lagos, Portugal) allowed the excavation of a deposit of waste dating from 15th-17th centuries. Among discarded objects, an important amount of human skeletal remains was exhumed (N=158 individuals). The archaeological and historical context, as well as the morphometric analysis of the skulls led us to attribute them an African origin. While historical sources document the trade of slaves by the Portuguese since the 15th century, so far no slave cemetery was excavated in Portugal. The study of their lives and deaths has been accomplished by historical documents. Therefore, this sample provides a unique opportunity to learn more about captive individuals who were brought to Portugal in the modern period. The present work focuses in the intentional dental modifications presented by several of these individuals. A total of 113 subjects have teeth that can be evaluated for the presence of intentional modifications. Of these, 55.8% individuals present dental modifications on their anterior dentition, 42.9% exhibiting modifications on both upper and lower teeth. The incisors were the most frequently modified teeth, followed by the canines. Both men and women as adults and sub-adults have dental intentional modifications. In most individuals dental modifications involved the removal of the mesial and distal angles, which is comparable to sub-Saharan African practices. However, we cannot infer a more specific origin for these slaves only based on dental modification’s type and pattern because several ethnic groups modify teeth in the same way.